2013
DOI: 10.4236/as.2013.43021
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen recovery and agronomic efficiency of forages with nitrogen fertilization under flooded condition

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
5
0
1
Order By: Relevance
“…In treatments that received no rescue N applications, waterlogging reduced ARE by 21% compared to non-waterlogged treatments in 2013 ( Figure 6). Previous studies have observed a decrease in ARE due to waterlogging [54,55]. Sigua et al (2013) found that ARE was reduced for two of three forage species studied in a greenhouse due to continuous waterlogging for 84 days [55].…”
Section: Apparent N Recovery Efficiencymentioning
confidence: 84%
See 1 more Smart Citation
“…In treatments that received no rescue N applications, waterlogging reduced ARE by 21% compared to non-waterlogged treatments in 2013 ( Figure 6). Previous studies have observed a decrease in ARE due to waterlogging [54,55]. Sigua et al (2013) found that ARE was reduced for two of three forage species studied in a greenhouse due to continuous waterlogging for 84 days [55].…”
Section: Apparent N Recovery Efficiencymentioning
confidence: 84%
“…Previous studies have observed a decrease in ARE due to waterlogging [54,55]. Sigua et al (2013) found that ARE was reduced for two of three forage species studied in a greenhouse due to continuous waterlogging for 84 days [55]. Similarly, Ren et al (2017) reported that waterlogging for six days at V3 reduced corn N use efficiency by 19% which resulted in lower corn yields due to inhibition of N transport and assimilation [22].…”
Section: Apparent N Recovery Efficiencymentioning
confidence: 91%
“…Computation of water and nitrogen productivity (WP and NP): Water productivity [WP (kg mm -1 )] was calculated by the dividing the linseed yield by the total water used (sum of applied water and effective rainfall), whereas, irrigation water productivity [IWP (kg mm -1 )] was calculated by the dividing the linseed yield by the irrigation water used. Nitrogen productivity [NP (seed yield kg ha -1 per kg N ha -1 applied)] or agronomic efficiency (AE) is the economic yield per unit of N applied are calculated by following formula used by Siqua et al (2013): NP (kg, kg -1 N) = Seed yield in fertilized plot (kg ha -1 ) -Seed yield in control plot (kg ha -1 ) / N applied (kg ha -1 )…”
Section: Methodsmentioning
confidence: 99%
“…Transient N deficiency occurred in wheat due to waterlogging stress, even when the plants were supplied with N at the time of planting (Robertson, Zhang, Palta, Colmer, & Turner, 2009). Reduction in N uptake, N recovery, and agronomic efficiency due to waterlogging was also observed in cotton and Bahiagrass ( Paspalum notatum ; Hodgson & MacLeod, 1988; Sigua, Williams, Chase Jr, Grabowski, & Kongchum, 2013). The decrease in the greenness (17–27 SPAD units) of corn leaves (as measured with chlorophyll leaf meter) with an increase in flooding duration from 1 to 7 d at the V6 growth stage of corn (Figure 6) was observed by Kaur et al.…”
Section: Effects Of Waterlogging On Soil and Nitrogen Availabilitymentioning
confidence: 88%